Efficient Ni and Fe doping process in ZnO with enhanced photocatalytic activity: A theoretical and experimental investigation. (August 2022) - Lemos, Samantha Custódio Silva; Rezende, Thaís Karine de Lima; Assis, Marcelo; Romeiro, Fernanda da Costa; Peixoto, Diego Alves; Gomes, Eduardo de Oliveira; Jacobsen, Gabriel Marques; Teodoro, Marcio Daldin; Gracia, Lourdes; Ferrari, Jefferson Luis; Longo, Elson; Andrés, Juan; et al.
Highlights: Excellent photodegradation of RhB and 4-NP were achieved by the Zn0.96 Ni0.04 O and Zn0.99 Fe0.01 O. The dopant ions inhibited the particle growth and flower-like morphology formation. Electron-hole separation and transport within the gap were affected by Ni 2+ and Fe 3+ . DFT elucidated the distinct effects of the dopant´s 3d levels within the ZnO band gap. The optimal dopant´s amount results in states that boost the photocarrier transport. Abstract: Zn1-x Nix O and Zn1-x Fex O structures were synthesized by the microwave-assisted hydrothermal method. The best photocatalytic degradation of rhodamine B (RhB) and 4-nitrophenol (4-NP) were achieved by the Zn0.96 Ni0.04 O and Zn0.99 Fe0.01 O. The specificity of each dopant showed significance in the positions of the impurity energy levels, which ended up influencing the electron-hole separation and transport, as demonstrated by the photoluminescence emissions. The morphological analysis revealed that besides inhibiting the growth of particles, the incorporation of dopant ions into the ZnO lattice triggered a nucleation process, consequently changing their morphology. Density functional theory (DFT) calculations showed that the Fe 3+ 3d orbitals generate energy levels below the conduction band (CB) while for Ni 2+, the levels were found to be spread in a broad energy range above the valence band (VB). The synergistic effect of band gaps alteration, inhibition of electron-hole pair recombination and appearance of new trapping energy sites justifies the superior photocatalytic activity. Graphical abstract: Excellent photodegradation of RhB and 4-NP were achieved derived from the distinct effects of the Fe 3+ and Ni 2+ dopant´s 3d levels within the ZnO band gap as showed by DFT. Image, graphical abstract